Seleno-polymannuronate attenuates neuroinflammation by suppressing microglial and astrocytic activation. (December 2018) - Bi, Decheng; Lai, Qiuxian; Han, Qingguo; Cai, Nan; He, Hanxing; Fang, Weishan; Yi, Jiang; Li, Xiaofan; Xu, Hong; Li, Xiuting; Hu, Zhangli; Liu, Qiong; et al.
Graphical abstract: Highlights: Se-PM inhibits the LPS-stimulated generation of inflammatory mediators in primary glial cells. Se-PM suppresses the LPS-induced activation of NF-κB and MAPK signalling. Se-PM attenuates the LPS-induced activation of microglia and astrocytes in the mouse brain. Abstract: Polymannuronate (PM) is an acidic polymer separated from alginate. PM is a linear block polysaccharide in edible brown algae that has been widely used in the food industry. Seleno-polymannuronate (Se-PM) is a seleno-derivative of PM synthesized from PM and Na2 SO3 in our laboratory. We investigated the anti-neuroinflammatory activity of Se-PM in lipopolysaccharide (LPS)-activated primary microglia and astrocytes and a mouse model of acute inflammation. Our results show that Se-PM could markedly reduce NO and PGE2 production, iNOS and COX-2 expression, and TNF-α, IL-1β and IL-6 secretion in LPS-treated primary microglia and astrocytes. Moreover, the LPS-triggered overactivation of NF-κB and MAPK signalling was attenuated by Se-PM. In addition, in vivo, LPS-induced microglial and astrocytic activation was remarkably suppressed by Se-PM. These results suggest that Se-PM merits exploration as an alternative medicinal or functional food for alleviating neuroinflammation.